Pascal ve Sağduyunun Çağrısı: İnanmanın Rasyonelliği/Pascal and the Call of Common Sense: The Rationality of Belief - Bayram Çınar (Oksident, 2025)
Within a theistic framework, arguments regarding the existence or nonexistence of God require a certain level of intellectual background on the part of the interlocutor. These arguments gain coherence only through specific process of reasoning and arise from accumulated observations and experiences. Belief and disbelief thus form a conviction within the individual. The teleological and cosmological arguments are derived from the notion that the order of the universe necessitates a designer. Consequently, every individual who professes belief reaches a particular level of consciousness, inspired by the universe’s order, and expresses a conviction. The question “Is belief in God more rational and aligned with common sense than disbelief?” constitutes the philosophical and theological foundation of this inquiry. While the argument in question does not constitute definitive proof of God's existence, it functions as a mechanism that motivates individuals toward belief. This approach, which assumes that common sense inclines individuals toward faith, is not confined to any particular culture or geography. On the contrary, this inclination represents a universal attitude. Therefore, this stance may manifest in various forms across different cultures and regions. Based on the premise that humans are rational beings, this orientation is also closely related to the principle of utilitarianism. Traces of this approach can be found in the early phases of the Muslim tradition. However, despite its presence in Islamic thought, it did not evolve into a systematic and traceable methodology. As a result, it failed to gain a widespread acceptance over the course of history. Furthermore, the absence of methodological structure suggests that its emergence may have been coincidental. This approach resurfaced in the West during the 17th century, this time as an extension of probability theory, and sought interlocutors within the theological domain. The rational theological framework developed by Pascal assumed the role of establishing the rational foundation of belief within theological discourse. In the form introduced by Pascal, this approach is based on the premise that belief is more rational for human beings. By constructing reasonable justifications for interlocutors, it aims to demonstrate that belief benefits the individual. Over time, this theological-philosophical approach fostered various interactions, leading to its integration with William James's pragmatism theory. James's perspective asserts that “what is useful is true for humans,” a notion that provides a meaningful common ground with Pascal's approach. This article does not aim to evaluate the potential religious implications of this perspective in either the East or the West; rather it seeks to elucidate the nature of this approach.